Does selective evaluation of gastric aspirates in preterm infants influence time to full enteral feeding?. (28th July 2020) - Kennedy, Lydia; Rogerson, Thomas; Keir, Amy Kate
Abstract : The use of routine gastric aspiration in the assessment of feeding intolerance is widespread in neonatal practice. Our article seeks to answer the clinical question, 'In premature infants receiving feeds via nasogastric or orogastric tube [P], does routine evaluation of gastric aspirates [I] compared with selective evaluation of gastric aspirates [C] reduce the time taken to establish full feeds without complications [O]?' Articles were identified through MEDLINE and reference lists from the sources found were reviewed for additional publications. Three papers were critically appraised and National Health and Medical Research Centre grades of level of evidence have been assigned to each. We found limited evidence to either support or reject the practice of routine gastric aspiration in preterm infants. There were no increases in the rates of significant complications in studies underpowered for this outcome. The decision to perform routine or selective gastric aspiration should be determined by individual centres. A large scale randomised controlled trial would be of significant benefit in determining the value of routine gastric aspiration in preterm infants.